2020
DOI: 10.2131/jts.45.227
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiolic acid dampens the expression of cyclooxygenase-2 in MDA-MB-231 breast cancer cells: Possible implication of the peroxisome proliferator-activated receptor β/δ abrogation

Abstract: A growing body of experimental evidence strongly suggests that cannabidiolic acid (CBDA), a major component of the fiber-type cannabis plant, exerts a variety of biological activities. We have reported that CBDA can abrogate cyclooxygenase-2 (COX-2) expression and its enzymatic activity. It is established that aberrant expression of COX-2 correlates with the degree of malignancy in breast cancer. Although the reduction of COX-2 expression by CBDA offers an attractive medicinal application, the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Interestingly, further in vivo studies have confirmed the antitumoral effect of cannabinoids since encouraging results such as reduction in the rate of growth and size of the tumors were reported [ 321 , 322 ]. The same antiproliferative effects were also reported in breast cancer together with the reduction of cell viability, alteration of signaling pathways and impeding cell cycle and promoting apoptosis [ 325 , 326 , 327 , 328 , 329 , 330 ]. Reduction of both tumoral volume and metastases have been also reported in in vivo studies [ 330 ].…”
Section: Cannabinoid Implications In Age-related Oncological Diseasessupporting
confidence: 62%
See 1 more Smart Citation
“…Interestingly, further in vivo studies have confirmed the antitumoral effect of cannabinoids since encouraging results such as reduction in the rate of growth and size of the tumors were reported [ 321 , 322 ]. The same antiproliferative effects were also reported in breast cancer together with the reduction of cell viability, alteration of signaling pathways and impeding cell cycle and promoting apoptosis [ 325 , 326 , 327 , 328 , 329 , 330 ]. Reduction of both tumoral volume and metastases have been also reported in in vivo studies [ 330 ].…”
Section: Cannabinoid Implications In Age-related Oncological Diseasessupporting
confidence: 62%
“…The same antiproliferative effects were also reported in breast cancer together with the reduction of cell viability, alteration of signaling pathways and impeding cell cycle and promoting apoptosis [ 325 , 326 , 327 , 328 , 329 , 330 ]. Reduction of both tumoral volume and metastases have been also reported in in vivo studies [ 330 ]. Moreover, in a recent paper aiming to evaluate the cancer risk in cannabis users, Clark et al reported that several types of head and neck cancer occur less frequently in this population suggesting that the ECS may represent a promising approach for the management of cancer [ 331 ].…”
Section: Cannabinoid Implications In Age-related Oncological Diseasessupporting
confidence: 62%
“…Transfection and Dual-Luciferase Assay The experiments were performed as described previously, with minor modification. 11,16,17) In brief, 24 h before transfection, MCF-7 cells (5 × 10 4 cells) were seeded onto 24-well plates containing MEMα. The DNA mixtures containing 300 ng of pGL4.49[luc2P/TCF-LEF RE/Hygro] plasmid (Promega, Madison, WI, U.S.A.) and 2 ng of the Renilla luciferase reporter plasmid were transfected using Lipofectamine ® LTX with PLUS reagent (Thermo Fisher Scientific, Waltham, MA, U.S.A.) in 24-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Although less active than CBD when assayed in HL60 (promyelocytic leukemia) and in CEM (promyelocytic leukemia) cells, remarkable activity was observed against MDA-MB-231 cells, a highly aggressive line of triple-negative breast cancer cells [ 37 ]. The activity was related to the attenuation of the transcriptional activity of PPARβ/δ, both expressed in MDA-MB-23 cells [ 38 ] and of AP-1 [ 39 ]. A cannabis extract rich in CBGA showed cytotoxic activity against colon cancer and human leukemia cells.…”
Section: Discovery Studiesmentioning
confidence: 99%